2023
DOI: 10.21070/jims.v4i0.1557
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Interpersonal Communication in Motivating Student Learning at Muhammadiyah 2 Sidoarjo Elementary School during the Covid-19 Pandemic

Abstract: This study aims to formulate problems regarding teacher interpersonal communication in motivating student learning along with what are supporting and inhibiting factors of teacher-student interpersonal communication during the covid-19 pandemic. The research method used is qualitative with data collection techniques through observation, interviews, and documentation. With the techniques of determining the informant using purposive sampling technique. The result showed that the teacher’s role was crucial in int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…Dalam menghadapi pandemi COVID-19 ini, Pemerintah Indonesia menetapkan protokol pencegahan penyebaran COVID-19 antara lain adalah penerapan 5M (mencuci tangan, menggunakan masker, menjaga jarak, menjauhi kerumunan dan mengurangi mobilitas) (2). Melaksanakan work form home merupakan bagian penerapan menjaga jarak, menjauhi kerumunan dan mengurangi mobilitas yang mana hal ini Salah satu upaya pengendalian yang juga dilakukan oleh Perusahaan X adalah dengan melalukan pengaturan work from home (3).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Dalam menghadapi pandemi COVID-19 ini, Pemerintah Indonesia menetapkan protokol pencegahan penyebaran COVID-19 antara lain adalah penerapan 5M (mencuci tangan, menggunakan masker, menjaga jarak, menjauhi kerumunan dan mengurangi mobilitas) (2). Melaksanakan work form home merupakan bagian penerapan menjaga jarak, menjauhi kerumunan dan mengurangi mobilitas yang mana hal ini Salah satu upaya pengendalian yang juga dilakukan oleh Perusahaan X adalah dengan melalukan pengaturan work from home (3).…”
Section: Pendahuluanunclassified
“…Penularan juga dapat terjadi melalui benda dan permukaan yang terkontaminasi droplet di sekitar orang yang terinfeksi (6). Oleh karena itu, penularan virus COVID-19 dapat terjadi melalui kontak langsung dengan orang yang terinfeksi dan kontak tidak langsung dengan permukaan atau benda yang digunakan pada orang yang terinfeksi (misalnya, handle pintu, tombol lift, printer, dll) di tempat kerja Perusahaan X. Dari halaman resmi CDC (Centers of Disease Control & Prevention), menjaga jarak (setidaknya 1.8meter), menghindari kerumuran dan kondisi ruang kerja tertutup dengan sirkulasi udara yang tidak baik merupakan upaya melindung diri dan orang lain dari Covid-19 (3). Pemerintah Indonesia juga telah menetapkan Peraturan Pemerintah No.…”
Section: Pendahuluanunclassified
“…The low implementation of this aspect of the protocol cannot be separated from the culture of the community before the pandemic, which carried out many joint activities. Then, in a study conducted by Sari and Sutisna (2021), it was found that the statement "Do not travel and gather with many people, unless it is important" also has a percentage of "always" answers which is only 26%.…”
Section: Avoiding the Crowdmentioning
confidence: 99%